Gender differences in desired quality of mates among young employed adults in Iloilo City - Banzuelo, Mariddie L.; Calibjo, Marie Tonnie O.
This study measured the relationship between the variables as mentioned, gender and desired qualities in mates.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Gender